Politik Minyak dalam Konflik Suriah - Kibtiah, Tia Mariatul (UI Scholars Hub, 2014)
The dynamics of conflict in Syria has influenced the energy security in the region. United States and Europe both have strategic interests on Syrian for securing the flow of oil and gas from the Middle East to Europe and preserving peace and harmony in the region. This article contends that Syria plays a strategic role in maintaining the stability of oil production from the Middle East. Even though the production of oil in Syria declined drastically from 400,000 barrell per day to 25,000 barrell per day, but most of those products are at the hand of opposition, including the jihadist of ISIS, in the Northern and Southern area of Syria. In addition, the presence of foreign fighters in Syrian civil war have fueled the conflict and affected the stability of the region. Syria needs at least 30 years to recover from current conflict and it needs oil productions as the vital factor. This article is based on interviews conducted in 2012 to 2013 in Jakarta and analysis of documents.